Perlindungan Objek Sipil Dalam Peristiwa Penyerangan Rumah Sakit Pada Konflik Bersenjata Internasional - Angriani, Lysa; Anwar, Arman; Peilouw, Johanis Steny Franco (PATTIMURA Law Study Review, 2025)
: International Humanitarian Law was created for humanitarian reasons to limit the consequences of armed conflict. Provisions in International Humanitarian Law prohibit all forms of attacks, repressive measures, or violence against civilian objects; this includes hospitals, which receive special protection. Regulations on the protection of hospitals as civilian objects are based on Article 19 of the Geneva Convention I, Article 22 of the Geneva Convention II, and Article 27 of the Hague Convention IV. Violations of these are categorized as war crimes based on Article 8 paragraph 2 letter b number ix of the 1998 Rome Statute. War crimes, in this case Israel carrying out attacks on Palestinian hospitals in Gaza, can be tried in accordance with the jurisdiction of the ICC and with the authority of the UN Security Council if Israel cannot carry out law enforcement processes in accordance with its national law.